Ethylene-vinyl alcohol copolymer composition and composite fabric comprising same

By introducing maleic acid monomer units and metal ions into the ethylene-vinyl alcohol copolymer, the problem of poor bonding between the copolymer and the fabric is solved, and a composite fabric with high water washing resistance and good surface characteristics is achieved.

CN119638877APending Publication Date: 2025-03-18CHANG CHUN PETROCHEMICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311192944.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The ethylene-vinyl alcohol copolymer is difficult to closely engage with the fabric when distributed on the fabric, resulting in a significant reduction in its cooling characteristics after multiple washes, limiting its application in the textile industry.

Method used

A modified ethylene-vinyl alcohol copolymer composition is provided, including maleic acid monomer units and metal ions, through which the bonding force of the composition to the fabric is enhanced and its washing resistance is improved.

Benefits of technology

After the modified ethylene-vinyl alcohol copolymer composition is distributed on the fabric, it can significantly improve its water-resistant effect, ensure that the change rate of cooling parameters is less than or equal to 5%, while maintaining good surface characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004451264120000141
    Figure BDA0004451264120000141
  • Figure BDA0004451264120000151
    Figure BDA0004451264120000151
  • Figure BDA0004451264120000161
    Figure BDA0004451264120000161
Patent Text Reader

Abstract

The present invention provides an ethylene vinyl alcohol copolymer (EVOH) composition, which comprises an ethylene vinyl alcohol copolymer modified by a maleic acid monomer unit and a metal ion, and is characterized in that the metal ion is a metal ion, and the ethylene vinyl alcohol copolymer modified by the maleic acid monomer unit is an ethylene vinyl alcohol copolymer modified by the maleic acid monomer unit, and the metal ion is an ethylene vinyl alcohol copolymer modified by the maleic acid monomer unit. The invention also provides a composite fabric, the composite fabric is provided with the composition distributed on a fabric, and the change rate of cool feeling parameters of the composite fabric after water washing is less than or equal to 5%. The invention further provides a composite fiber which comprises a fiber and the composition, and the fiber is impregnated by the composition, so that the composition is distributed on the fiber. The ethylene-vinyl alcohol copolymer composition disclosed by the invention is distributed on fabrics or fibers, so that the influence of washing on the cool feeling characteristic is reduced, the washing resistance effect is further improved, and the fabric or fibers have good surface characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an ethylene-vinyl alcohol copolymer composition and a composite fabric containing the same; however, the present invention is not limited thereto. Background Art

[0002] Ethylene vinyl alcohol copolymer (EVOH) has good transparency, gas barrier properties, solvent / oil resistance, and mechanical strength, so it is widely used in laminates that can store perishable items; for example, EVOH and laminates are often used in the food packaging industry, medical equipment and consumables industry, pharmaceutical industry, electronics industry, and agricultural chemical industry. Specifically, EVOH is often added to laminates to form a unique layer as an oxygen barrier layer.

[0003] At the same time, ethylene-vinyl alcohol copolymer also has good bioaffinity and skin-friendly cooling properties; it can be used not only in hemodialysis membranes, but also in textile products, for example: it can be set on fabrics to make functional composite fabrics such as cooling clothes and quick-drying clothes. Summary of the invention

[0004] However, although the EVOH composition has good skin-friendly cooling properties, the inventors have found that it is difficult for the EVOH composition to bond tightly to the fabric when distributed on it, so that the cooling properties of the finished composite fabric will be significantly affected after multiple washings, which in turn leads to the fact that the application of EVOH composition in the textile industry is still limited.

[0005] To solve the above technical problems, the present invention provides an ethylenevinyl alcohol copolymer (EVOH) composition, which includes an ethylenevinyl alcohol copolymer modified with a maleic acid monomer unit and a metal ion.

[0006] According to one embodiment of the present invention, the content of the maleic acid monomer unit is 0.05 to 0.49 mole %.

[0007] According to one embodiment of the present invention, the content of the maleic acid monomer unit is 0.1 to 0.49 mole %.

[0008] According to an embodiment of the present invention, the content of the metal ions is 0.05 to 100 ppm.

[0009] According to one embodiment of the present invention, the content of the metal ions is 0.1 to 80 ppm.

[0010] According to an embodiment of the present invention, the metal ions are copper ions.

[0011] According to an embodiment of the present invention, the metal ion is a divalent copper ion.

[0012] According to one embodiment of the present invention, the ethylene content of the composition is 24 to 48 mole %.

[0013] According to one embodiment of the present invention, the saponification degree of the composition is greater than 99.5 mole %.

[0014] According to an embodiment of the present invention, the volatile matter of the composition is 10 to 90%.

[0015] Another aspect of the present invention provides a composite fabric, comprising: a fabric; and the composition as described above, which is distributed on the fabric. The cooling parameter change rate of the composite fabric after washing is less than or equal to 5%; specifically, the cooling parameter is measured according to FTTS-FA-019-2013, and the cooling parameter change rate after washing is obtained according to the following formula: [|L0-L30| / L0]*100%; wherein L0 is the cooling parameter after 0 washings, L30 is the cooling parameter after 30 washings, and the washing is performed according to JIS L 0217-130.

[0016] According to one embodiment of the present invention, the composition is coated on a surface of the fabric.

[0017] According to one embodiment of the present invention, the composition impregnates the fabric so that the composition is distributed on the fabric.

[0018] According to an embodiment of the present invention, the fabric is woven from any one of nylon, polyethylene, polyester, rayon, natural fibers or a mixture thereof.

[0019] According to one embodiment of the present invention, the composition is formulated into a 3 to 10 wt % solution and then distributed on the fabric.

[0020] Another aspect of the present invention provides a composite fiber, which comprises a fiber and the composition as described above; wherein the composition is impregnated into the fiber so that the composition is distributed on the fiber.

[0021] In yet another aspect, the present invention provides a fabric comprising the aforementioned composite fiber.

[0022] The advantages of the present invention are that the ethylene-vinyl alcohol copolymer composition of the present invention is distributed on fabrics or fibers to reduce the influence of water washing on the cooling property, thereby improving the water washing resistance, and also has good surface properties. DETAILED DESCRIPTION

[0023] The following embodiments should not be considered to overly limit the present invention. Those skilled in the art may modify and change the embodiments discussed herein without departing from the spirit or scope of the present invention, and still fall within the scope of the present invention.

[0024] In this document, unless the context otherwise states, the terms "comprise", "include", "have" or "contain" are inclusive or open, and do not exclude other undescribed elements or method steps; the terms "a" and "the" can be interpreted as singular or plural; the term "one or more" means "at least one", and thus can include a single feature or a mixture / combination. In addition, in this specification and claims, unless otherwise stated, "distributed on something" can be regarded as directly or indirectly contacting the surface of something by attachment or other forms, and the definition of the surface should be judged according to the context / paragraph meaning of the specification content and the common knowledge in the field to which the specification belongs.

[0025] One aspect of the present invention provides an ethylene-vinyl alcohol copolymer (EVOH) composition, which includes an ethylene-vinyl alcohol copolymer modified with a maleic acid monomer unit and a metal ion.

[0026] The "maleic acid monomer unit" described in this case is a monomer unit derived from maleic acid, maleic anhydride, monomethyl maleate, monoethyl maleate or diethyl maleate; in a preferred embodiment, the maleic acid monomer unit is derived from maleic anhydride. Without being limited by a specific theory, the inventors have found that by adding maleic acid monomer units when generating EVOH to make it an ethylene-vinyl alcohol copolymer modified with maleic acid monomer units (also known as "EVOH modified with maleic acid"), the EVOH composition can generate groups with strong interaction with fabrics / fibers, thereby strengthening the tightness of the bonding between the composition and the fabrics / fibers and improving the water washing resistance of the finished composite fabric.

[0027] The "metal ion" described herein refers to a metal ion that can form a coordination bond with a maleic acid monomer to stabilize the polymer molecule, without any particular limitation, wherein in the preferred embodiment of the present invention, it is a copper ion, for example: a monovalent copper ion, a divalent copper ion, a trivalent copper ion or a tetravalent copper ion; more preferably, the metal ion is a divalent copper ion. Without being limited by a specific theory, the inventors further found that the addition of maleic acid monomer units can improve the water washing resistance of the finished composite fabric, but the monomer units may produce a self-crosslinking reaction, causing the surface of the finished composite fabric to produce a gel, resulting in poor surface properties. After further experiments by the inventors, it was found that if metal ions are added to the EVOH composition, the overall EVOH composition can be effectively stabilized and prevented from deteriorating, thereby making the surface of the finished composite fabric smooth. In other words, the EVOH composition of the present invention containing both maleic acid monomer units modified ethylene-vinyl alcohol copolymer and metal ions distributed on the fabric / fiber can not only effectively improve the water washing resistance, but also have good surface properties at the same time.

[0028] According to at least one embodiment of the present invention, the content of the maleic acid monomer unit is 0.05 to 0.49 mole%, for example, but not limited to any two of the following values: 0.05 mole%, 0.06 mole%, 0.07 mole%, 0.08 mole%, 0.09 mole%, 0.1 mole%, 0.13 mole%, 0.16 mole%, 0.19 mole%, 0.2 mole%, 0.23 mole%, 0.26 mole%, 0.29 mole%, 0.3 mole%, 0.33 mole%, 0.36 mole%, 0.39 mole%, 0.4 mole%, 0.43 mole%, 01.46 mole% and 0.49 mole%. In a preferred embodiment, the content of the maleic acid monomer unit is 0.1 to 0.49 mole%.

[0029] According to at least one embodiment of the present invention, the content of the metal ion is 0.05 to 100 ppm, for example but not limited to between any two of the following values: 0.05 ppm, 0.1 ppm, 0.5 ppm, 1 ppm, 5 ppm, 10 ppm, 15 ppm, 20 ppm, 25 ppm, 30 ppm, 35 ppm, 40 ppm, 45 ppm, 50 ppm, 55 ppm, 60 ppm, 65 ppm, 70 ppm, 75 ppm, 80 ppm, 85 ppm, 90 ppm, 95 ppm and 100 ppm; in a preferred embodiment, the content of the metal ion is 0.1 to 80 ppm.

[0030] According to at least one embodiment of the present invention, the ethylene-vinyl alcohol copolymer modified with maleic acid monomer units has an ethylene content of 24 to 48 mole%, for example, but not limited to, between any two of the following values: 24 mole%, 25 mole%, 26 mole%, 27 mole%, 28 mole%, 29 mole%, 30 mole%, 31 mole%, 32 mole%, 33 mole%, 34 mole%, 35 mole%, 36 mole%, 37 mole%, 38 mole%, 39 mole%, 40 mole%, 41 mole%, 42 mole%, 43 mole%, 44 mole%, 45 mole%, 46 mole%, 47 mole% and 48 mole%.

[0031] According to one embodiment of the present invention, the saponification degree of the ethylene-vinyl alcohol copolymer modified with maleic acid monomer units is greater than 99.5 mole%, for example but not limited to: greater than 99.5 mole%, greater than or equal to 99.6 mole%, greater than or equal to 99.7 mole%, greater than or equal to 99.8 mole%, or greater than or equal to 99.9 mole%.

[0032] The composition of the present invention generally has a specific range of volatiles, for example, the volatiles of the composition are 10 to 90%, for example but not limited to any two of the following values: 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% and 90%. The volatiles are the final ethylene-vinyl alcohol copolymers obtained by analyzing the ISO 14663-2 Annex A method.

[0033] The EVOH composition of the present invention may be in the form of particles, films, fibers, solutions, etc. According to at least one embodiment of the present invention, the EVOH composition of the present invention is in the form of particles, and it is the form and / or shape of one or more particles formed by granulation of the EVOH composition. Although the EVOH composition in the form of one or more particles formed by granulation is described herein, the EVOH composition may also be processed into the form of beads, cubes, fragments, shavings, etc. In some embodiments, the particle shape of the EVOH composition may be columnar, spherical, or flat; wherein the columnar shape may be cylindrical, elliptical, or angular, and the spherical shape may be spherical, elliptical, or go-shaped.

[0034] Another aspect of the present invention provides a composite fabric, comprising: a fabric; and a composition as described above, which is distributed on the fabric. The rate of change of the coolness parameter of the composite fabric after washing is less than or equal to 5%, for example but not limited to: 5%, 4.5%, 4%, 3.5%, 3%, 2.5%, 2%, 1.5% or 1%. Specifically, the present invention evaluates the washability of the fabric by testing the rate of change of the coolness parameter of the fabric after washing. The coolness parameter refers to the maximum heat loss value (W / cm2) per unit area when an instrument is used to simulate the contact of the fabric with the human body surface. 2 ) as an indicator of the cooling performance of the fabric; the cooling parameter in this article is measured according to FTTS-FA-019-2013, and the cooling parameter change rate after washing is obtained according to the following formula: [|L0-L30| / L0]*100%; wherein L0 is the cooling parameter after 0 washings, L30 is the cooling parameter after 30 washings, and the washing is carried out according to JIS L 0217-103.

[0035] After multiple washings, the cool feeling parameters of the composite fabric of the present invention have a certain range of change rate (ie, less than or equal to 5%) compared to before washing; in other words, the composite fabric of the present invention has a certain degree of water-resistant effect.

[0036] The "fabric" described herein refers to a finger fabric or any of the fabrics; preferably, it is made of a texture with high thermal conductivity that absorbs heat quickly, such as but not limited to: any of nylon, polyethylene fiber, polyester fiber, polyamide fiber, polyacrylonitrile fiber, polypropylene fiber, rayon, natural fiber (cotton, linen, wool, etc.) with high thermal conductivity, or a mixed fiber material thereof; in a preferred embodiment, the fabric is woven from any of nylon, polyethylene, polyester, rayon, natural fiber, or a mixture thereof. The weaving structure of the fabric is not particularly limited, and can be various weaving forms such as plain weave, damask weave, satin weave, leno weave, imitation leno weave, twill weave, etc.

[0037] According to one embodiment of the present invention, the composition is applied to a surface of the fabric. According to another embodiment of the present invention, the composition is impregnated with the fabric so that the composition is distributed on the fabric. The concentration of the composition is not limited. After experiments, it is found that forming a low-concentration composition solution can reduce the amount of the composition while still providing the fabric with water-resistant and cool properties. Specifically, it is preferred that the composition is formulated into a 3 to 10 wt% solution (for example, but not limited to any two of the following values: 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt%, 9 wt%, 9.5 wt% and 10 wt%), and then applied or impregnated with the fabric. The composition is configured as a solution, and the solvent that can be used is not particularly limited as long as it can dissolve or disperse the EVOH composition; in terms of safety (such as boiling point or toxicity), subsequent drying steps or ease of operation, water or alcohol aqueous solution (such as but not limited to methanol aqueous solution, ethanol aqueous solution, isopropanol aqueous solution, etc.) is preferred. After the composition forms a solution, it is coated or impregnated with the fabric, and the thickness formed is not particularly limited, and the required thickness can be adjusted as needed, for example, the thickness of the fabric after drying is 0.01 to 1 mm.

[0038] In another aspect, the present invention provides a composite fiber, which comprises a fiber and the composition as described above; wherein the composition is impregnated into the fiber so that the composition is distributed on the fiber. The "fiber" described herein refers to a fiber material that is not woven into a fabric, such as but not limited to spun fiber; preferably, the fiber comprises a high thermal conductivity material that absorbs heat quickly, such as but not limited to: any one of high thermal conductivity nylon, polyethylene fiber, polyester fiber, polyamide fiber, polyacrylonitrile fiber, polypropylene fiber, rayon, natural fiber (cotton, linen, wool, etc.), or a mixed fiber material thereof; in a preferred embodiment, the fiber comprises any one of nylon, polyethylene, polyester, rayon, natural fiber, or a mixture thereof.

[0039] According to one embodiment of the present invention, it is preferred that the composition is prepared into a 3 to 10 wt% solution (for example, but not limited to any two of the following values: 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt%, 9 wt%, 9.5 wt% and 10 wt%), and then impregnated into the fiber. Wherein, the composition is configured as a solution, and the solvent that can be used is not particularly limited as long as it can dissolve or disperse the EVOH composition; in terms of safety (such as from the perspective of boiling point or toxicity), subsequent drying steps or ease of operation, water or alcohol aqueous solution (for example, but not limited to methanol aqueous solution, ethanol aqueous solution, isopropanol aqueous solution, etc.) is preferred. After the composition forms a solution, it is impregnated into the fiber, so that the composite fiber has a core-shell structure, and the composite fiber can be further woven (for example, but not limited to winding or braiding) to form a fabric. In addition, the thickness of the composite fiber is also not particularly limited, and can be adjusted as required, for example, 0.001 to 1 mm. The thickness of the fabric formed by weaving the composite fiber is also not particularly limited, and can be adjusted as required, for example, 0.01 to 1 mm. Example

[0040] Hereinafter, the present invention will be further described with detailed description and examples. However, it should be understood that these examples are only used to help the present invention to be more easily understood and are not used to limit the scope of the present invention.

[0041] 1. Preparation of ethylene-vinyl alcohol copolymer (EVOH) composition

[0042] The following is a non-limiting method for preparing the EVOH compositions of the present invention, wherein the EVOH compositions of the 6 non-limiting examples (Examples 1-6) and the EVOH compositions of the 11 comparative examples (Comparative Examples 1-11) are all prepared by the following method (or a method similar to the following method).

[0043] First, maleic anhydride (specific usage is as follows), 1100 g of vinyl acetate, 182.3 g of methanol, 85 g of peroxidation initiator and 1.975 g of citric acid are added to a small-sized polymerization kettle equipped with a jacket. After the polymerization kettle is temporarily replaced with nitrogen, ethylene is replaced and pressed in until the ethylene pressure reaches a specific value (specific value is as follows). While maintaining the ethylene pressure, the temperature is raised to 60° C. while stirring to start polymerization. 8 hours after the start of polymerization, when the solid content reaches 40%, 46.6 kg of polymerization inhibitor is added. Thus, a maleic acid-ethylene-vinyl acetate copolymer having a specific maleic acid monomer unit content and ethylene content is obtained. Subsequently, the reaction solution containing the copolymer is supplied to a small-sized distillation tower, and methanol is added to raise the temperature to remove unreacted vinyl acetate, thereby obtaining a methanol solution of the copolymer and the maleic acid monomer unit, which is alkalized with NaOH at 55° C. to obtain a maleic acid-ethylene-vinyl alcohol copolymer having a saponification degree greater than 99.5%. The maleic acid-ethylene-vinyl alcohol copolymer particles are then separated by water washing to remove the unpolymerized third monomer. The particles are then impregnated with a copper acetate aqueous solution of a specific concentration for a specific time and then dehydrated to obtain maleic acid-ethylene-vinyl alcohol copolymer particles with a specific copper content. Finally, the volatile matter is adjusted to obtain the finished EVOH composition.

[0044] Using the above method, the amount of maleic anhydride used, ethylene pressure, copper acetate concentration and impregnation time (immersion time) in the process of each embodiment are different, resulting in different ethylene content, maleic acid monomer unit content and copper ion content; the specific differences are detailed as follows. Example 1

[0045] The preparation method of Example 1 is as described above. However, Example 1 uses 25.2 g of maleic anhydride and an ethylene pressure of 36.5 kg / cm 2 , the copper acetate concentration is 0.001wt% and the copper acetate impregnation time is 0.5 hour. Example 2

[0046] The preparation method of Example 2 is as described above. However, Example 2 uses 70.1 g of maleic anhydride and an ethylene pressure of 36.5 kg / cm 2 , the copper acetate concentration is 0.001wt% and the copper acetate impregnation time is 2.5 hours. Example 3

[0047] The preparation method of Example 3 is as described above. However, Example 3 uses 115.5 g of maleic anhydride and an ethylene pressure of 36.5 kg / cm2 , the copper acetate concentration is 0.020wt% and the copper acetate impregnation time is 24 hours. Example 4

[0048] The preparation method of Example 4 is as described above. However, Example 4 uses 120.3 g of maleic anhydride and an ethylene pressure of 48.0 kg / cm 2 , the copper acetate concentration is 0.040wt% and the copper acetate impregnation time is 16 hours. Example 5

[0049] The preparation method of Example 5 is as described above. However, Example 5 uses 70.5 g of maleic anhydride and an ethylene pressure of 60.0 kg / cm 2 , the copper acetate concentration is 0.020wt% and the copper acetate impregnation time is 10 hours. Example 6

[0050] The preparation method of Example 6 is as described above. However, Example 6 uses 70.1 g of maleic anhydride and an ethylene pressure of 60.0 kg / cm 2 , the copper acetate concentration is 0.020wt% and the copper acetate impregnation time is 10 hours.

[0051] Using the above method, the amount of maleic anhydride used, ethylene pressure, copper acetate concentration and impregnation time in the process (preparation process) of each comparative example are different, resulting in different ethylene content, maleic acid monomer unit content and copper ion content; the specific differences are detailed as follows. Comparative Example 1

[0052] The preparation method of Comparative Example 1 is as described above. However, in Comparative Example 1, the ethylene pressure is 36.5 kg / cm 2 , and no maleic anhydride and copper acetate were added. Comparative Example 2

[0053] The preparation method of Comparative Example 2 is as described above. However, in Comparative Example 2, 25.5 g of maleic anhydride and an ethylene pressure of 36.5 kg / cm 2 , and no copper acetate was added. Comparative Example 3

[0054] The preparation method of Comparative Example 3 is as described above. However, in Comparative Example 3, 114.8 g of maleic anhydride and an ethylene pressure of 36.5 kg / cm 2 , and no copper acetate was added. Comparative Example 4

[0055] The preparation method of Comparative Example 4 is as described above. However, in Comparative Example 4, 160.1 g of maleic anhydride and an ethylene pressure of 36.5 kg / cm 2 , the copper acetate concentration is 0.05wt% and the copper acetate impregnation time is 24 hours. Comparative Example 5

[0056] The preparation method of Comparative Example 5 is as described above. However, in Comparative Example 5, 160.3 g of maleic anhydride and an ethylene pressure of 36.5 kg / cm 2 , the copper acetate concentration is 0.04wt% and the copper acetate impregnation time is 16 hours. Comparative Example 6

[0057] The preparation method of Comparative Example 6 is as described above. However, in Comparative Example 6, 230.5 g of maleic anhydride and an ethylene pressure of 36.5 kg / cm 2 , the copper acetate concentration is 0.05wt% and the copper acetate impregnation time is 24 hours. Comparative Example 7

[0058] The preparation method of Comparative Example 7 is as described above. However, in Comparative Example 7, the ethylene pressure was 48.0 kg / cm 2 , and no maleic anhydride and copper acetate were added. Comparative Example 8

[0059] The preparation method of Comparative Example 8 is as described above. However, in Comparative Example 8, 229.8 g of maleic anhydride and an ethylene pressure of 48.0 kg / cm 2 , and no copper acetate was added. Comparative Example 9

[0060] The preparation method of Comparative Example 9 is as described above. However, in Comparative Example 9, the ethylene pressure was 60.0 kg / cm 2 , and no maleic anhydride and copper acetate were added. Comparative Example 10

[0061] The preparation method of Comparative Example 10 is as described above. However, in Comparative Example 10, 160.9 g of maleic anhydride and an ethylene pressure of 60.0 kg / cm 2 , the copper acetate concentration is 0.06wt% and the copper acetate impregnation time is 20 hours. Comparative Example 11

[0062] The preparation method of Comparative Example 11 is as described above. However, in Comparative Example 11, 70.8 g of maleic anhydride and an ethylene pressure of 60.0 kg / cm 2, the copper acetate concentration is 0.07wt% and the copper acetate impregnation time is 24 hours.

[0063] 2. Analysis and determination methods

[0064] The following provides various parameters and property measurement methods of the EVOH compositions of Examples 1-6 and Comparative Examples 1-11 and the composite fabrics made therefrom; further, Tables 1 and 2 specifically present the parameters and properties of each of the embodiments and comparative examples, as well as the characteristic evaluation of the composite fabrics thereof.

[0065] 2-1. Analysis method of ethylene content

[0066] In order to evaluate / analyze the ethylene content of the EVOH compositions of the embodiments / comparative examples, the present invention uses a Raman spectrometer manufactured by UniDRON and uses a laser light source with a wavelength of 473 nm to randomly measure the ethylene content of 5 sites in each EVOH composition sample, and then takes the average value as the ethylene content value of the EVOH composition sample.

[0067] 2-2. Determination of the content of maleic acid monomer units

[0068] About 2000 mg of EVOH composition was dissolved in 75 ml of dimethylacetamide (DMAc), and 2-3 drops of phenolphthalein were added as an indicator as an experimental group. Then, 0.1 M NaOH was used for titration. When the titration reached the endpoint, the amount of 0.1 M NaOH used was recorded. In addition, a group containing only DMAc solvent was used as a blank group. The amount used in the blank group was subtracted from the experimental group to infer the ratio of the maleic acid monomer unit.

[0069] 2-3. Determination of metal ion content

[0070] After drying the water-containing EVOH composition sample, take 0.2g of the sample and add 10ml of nitric acid to dissolve the sample (also known as wet decomposition). Then, dilute the decomposed liquid with ion exchange water to a total liquid volume of 50ml. Using an ICP emission spectrophotometer (Thermofisher iCAP TM 7400ICP-OES) was used to perform quantitative analysis of metals in the diluted solution; the content of metal compounds was calculated based on element conversion values. Furthermore, during the quantitative analysis, a calibration curve was prepared using a commercially available copper ion standard solution (ISE standard Cu).

[0071] 2-4. Determination of saponification degree

[0072] Herein, the saponification degree of each EVOH composition is measured according to the method of ISO 14663-2:1999.

[0073] 2-5. Analysis and evaluation of coating surface conditions

[0074] 40x25cm plain woven nylon fabric was used as the coated fabric (Q-MAX: 0.11W / cm 2 ), then the EVOH composition and an alcohol aqueous solution with a specific methanol to water ratio (as shown in the following table) are co-prepared into a solution with a concentration of 5wt%, and then coated with a scraper (wet coating thickness 0.1mm), and finally pre-dried at 60℃ for 5 minutes, dried at 120℃ for 5 minutes, and then fixed at 140℃ for 1 minute, to finally form a composite fabric product. When the surface condition of the composite fabric product is evaluated by naked eyes and hand touch, the one marked "O" represents a smooth coating range, and the one marked "X" represents gel residue on the fabric surface. Ethylene content (%) Methanol: Water weight ratio 29 6∶4 38 7∶3 44 8∶2

[0075] 2-6-1. Analysis and evaluation of water washability - coolness parameters

[0076] As described herein, the washability of the composite fabric is based on the rate of change of the cool feeling parameter after washing. First, regarding the determination of the cool feeling parameter, the present invention uses a thermal effect measuring instrument KES-F7THERMO LABO II or an equivalent test instrument to test according to the standard method FTTS-FA-019-2013. Here, the test sample is the same as the finished composite fabric in the previous paragraph and 5 pieces are taken, each piece is a 20cmx20 cm square (the measured area is 5cmx5cm); the test sample is placed in an environment with a temperature of 20±2°C and a relative humidity of 65±2%RH for 24 hours before testing. After confirming the parameters, heat the machine for about 15 minutes; set the temperature of the hot plate (Temperature-Box) to 35.0±0.1°C, and when it reaches 35.0±0.1°C, turn the guard heater (Guard Heater) switch to the start position (ON). Set the temperature of the cold plate (Water-Box) to 25.0±0.1℃ (simulating the external environment). When the temperature reaches 25.0±0.1℃, place the sample on the cold plate with the coated surface (applicable surface) of the EVOH composition facing upwards. When the temperature of the hot plate reaches the set temperature of 35.0±0.1℃, press the qm key and quickly place the hot plate on the sample. Record the qm value on the display. This value is the maximum heat loss value of the fabric at the moment of contact, that is, the experimental result of the cool feeling, and the unit is W / cm 2 .

[0077] 2-6-2. Analysis and evaluation of water washability - change rate of cooling parameters

[0078] After knowing the determination method of the cool feeling parameter, it is further necessary to analyze the change rate of the cool feeling parameter to evaluate the washability of the finished composite fabric. The formula of the change rate of the cool feeling parameter is: [|L0-L30| / L0]*100%; wherein L0 is the cool feeling parameter after 0 washings, and L30 is the cool feeling parameter after 30 washings; the one marked with "O" represents that the value of the change rate of the cool feeling parameter [|L0-L30| / L0]*100% is less than or equal to 5%; the one marked with "X" represents that the value of the change rate of the cool feeling parameter [1L0-L30| / L0]*100% is greater than 5%. In detail, the washing is carried out using Automatic Repeg Washing System.AWS-400B, or a test instrument of the same level, in accordance with the standard method JIS L 0217-103. The washing procedure of the composite fabric is as follows: washing with 40° C. water for 5 minutes, followed by draining for 2 minutes, dehydrating for 2 minutes, washing for 2 minutes, and finally dehydrating for 4 minutes to complete the washing steps.

[0079] Table 1

[0080] Table 2

[0081] According to the results presented in Table 1 and Table 2, it can be seen from Comparative Examples 1, 7 and 9 that when the EVOH composition does not contain maleic acid monomer units, even though the surface properties of the composite fabrics made therefrom are ideal, the water washing resistance is extremely poor; it can be seen from Comparative Examples 2 to 6, 8 and 10 to 11 that when maleic acid monomer units are contained, the composite fabric products all have good water washing resistance, but their surfaces may have poor surface properties due to the self-crosslinking reaction of the monomer units, resulting in the formation of gel.

[0082] As described herein, it is believed that while containing maleic acid monomer units, if the EVOH composition further contains metal ions, it can effectively stabilize the overall EVOH composition and prevent it from deteriorating, thereby making the surface of the finished composite fabric smooth. A detailed examination of Tables 1 and 2 shows that the EVOH compositions of Examples 1 to 6 all contain maleic acid monomer units and metal ions at the same time, so the composite fabrics made from these compositions all have good water-washing resistance and surface properties. However, from the comparison of Examples 5 and 6 with Comparative Example 11, it can be seen that even if maleic acid monomer units and metal ions are contained at the same time, if the metal ion content in Comparative Example 11 exceeds an upper limit, the surface properties of the finished composite fabric will still be poor; without being limited by a specific theory, it is believed that the result should be attributed to: when the metal ion content exceeds an upper limit, it will form impurities, resulting in the production of gel, thereby making the surface of the finished product not smooth. In addition, from the comparison between Example 4 and Comparative Example 5, it can be seen that when the content of maleic acid monomer units exceeds an upper limit, even if metal ions are contained at the same time, the surface properties are still not ideal; without being limited by a specific theory, it is believed that the result should be attributed to: the metal ion content is not enough to stabilize the composition containing too many maleic acid monomer units, and if the metal ion content is increased accordingly, it will further lead to the above-mentioned impurity situation.

[0083] In other words, as shown in Examples 1 to 6 of the present invention, the present invention preferably simultaneously controls the maleic acid monomer unit content of the EVOH composition to be 0.05 to 0.49 mole% and the copper metal content to be 0.05 to 100 ppm, so that the composite fabric obtained not only has good water wash resistance, but also exhibits ideal surface properties (its surface is smooth).

[0084] In summary, the EVOH composition of the present invention distributed on the fabric / fiber can not only reduce the influence of water washing on the cooling property, thereby improving the water washing resistance, but also has good surface properties.

[0085] Herein, all ranges provided are intended to include each specific range within a given range and combinations of sub-ranges between the given ranges. In addition, unless otherwise stated, all ranges provided herein include the endpoints of the ranges. Thus, ranges 1-5 specifically include 1, 2, 3, 4, and 5, as well as sub-ranges such as 2-5, 3-5, 2-3, 2-4, 1-4, etc.

[0086] All publications and patent applications cited in this specification are incorporated herein by reference, and each individual publication or patent application is specifically and individually indicated to be incorporated herein by reference for any and all purposes. In the event of any inconsistency between this document and any publication or patent application incorporated herein by reference, this document controls.

[0087] The present invention has been described in detail above. However, what is described above is only the preferred embodiment of the present invention and should not be used to limit the scope of implementation of the present invention. That is, all equivalent changes and modifications made according to the scope of the patent application of the present invention should still fall within the scope of the patent of the present invention.

Claims

1. An ethylene vinyl alcohol copolymer (EVOH) composition comprising an ethylene vinyl alcohol copolymer modified with a maleic acid monomer unit and a metal ion.

2. The composition according to claim 1, wherein the content of the maleic acid monomer unit is 0.05 to 0.49 mole%.

3. The composition of claim 1, wherein the content of the maleic acid monomer unit is 0.1 to 0.49 mole%.

4. The composition of claim 1, wherein the metal ion content is 0.05 to 100 ppm.

5. The composition of claim 1, wherein the metal ion content is 0.1 to 80 ppm.

6. The composition of claim 1, wherein the metal ions are copper ions.

7. The composition of claim 6, wherein the metal ion is a divalent copper ion.

8. The composition of claim 1, wherein the composition has an ethylene content of 24 to 48 mole %.

9. The composition of claim 1, wherein the degree of saponification of the composition is greater than 99.5 mole %.

10. The composition of claim 1, wherein the volatile content of the composition is 10 to 90%.

11. A composite fabric comprising: a fabric; and The composition according to any one of claims 1 to 10, distributed on the fabric; in, The change rate of the cooling parameter of the composite fabric after washing is less than or equal to 5%, wherein the cooling parameter is measured according to FTTS-FA-019-2013, and the change rate of the cooling parameter after washing is obtained according to the following formula: [|L0-L30| / L0]*100%; wherein L0 is the cooling parameter after 0 washings, and L30 is the cooling parameter after 30 washings; wherein the washing is carried out according to JIS L 0217-130.

12. The composite fabric of claim 11, wherein the composition is coated on a surface of the fabric.

13. The composite fabric of claim 11, wherein the composition impregnates the fabric so that the composition is distributed on the fabric.

14. The composite fabric according to claim 11, wherein the fabric is woven from any one of nylon, polyethylene, polyester, rayon, natural fibers or a mixture thereof.

15. The composite fabric according to claim 12 or 13, wherein the composition is formulated into a 3 to 10 wt% solution and then distributed on the fabric.

16. A composite fiber comprising a fiber and the composition according to any one of claims 1 to 10; wherein the fiber is impregnated with the composition so that the composition is distributed on the fiber.

17. A fabric comprising the composite fiber according to claim 16.